PERLINDUNGAN KONSUMEN DALAM PRAKTIK PENGEMBALIAN UANG KOIN DENGAN PERMEN(Studi Kasus Terhadap Usaha Retail Di Kota Purwokerto) - Tarisa Salsabila Putri; Aris Priyadi; Elisabeth Pudyastiwi; Elly Kristiani Purwendah (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2025)
Consumer protection in Indonesia is an important aspect of maintaining fairness and transparency in economic transactions. This study aims to examine the practice of returning change in the form of candy, which still frequently occurs in society, and its implications for consumer rights. The research method used is normative legal research with a qualitative approach, relying on secondary data from legislation, literature, and interviews with consumers and business actors. The results of the study indicate that the practice of returning change in the form of candy violates Law No. 8 of 1999 on Consumer Protection and Law No. 7 of 2011 on Currency. This practice creates legal uncertainty for consumers, financially harms them, and violates fundamental consumer rights, such as the right to receive clear information, the right to choose, and the right to be treated fairly. Additionally, this practice also poses potential health risks for consumers who cannot consume candy. This study suggests the need for increased public awareness of consumer rights, tighter government oversight of business actors, and consistent law enforcement to protect consumer rights. Thus, it is hoped that a fairer and more responsible business environment will be created, where consumer rights are respected and protected.